PENERAPAN METODE PENYUSUTAN MENURUT PSAK NO 16 - Daharang, Selvini (Jurnal Pitis AKP, 2019)
The role of Fixed Assets in supporting the company's operational activities is quite large. Furthermore, the value of invested assets remains relatively large. Thus, an error in valuing fixed assets will result in material error. Therefore, standards are written in PSAK No. 16 which regulates the recognition, measurement, cost after acquisition, depreciation, termination and presentation of fixed assets. The purpose of this study is to find out how the application of depreciation according to PSAK No. 16 Fixed asset depreciation methods are divided into 3, including the straight line method, the diminishing balance method, and the ssum of the unit method. The straight-line method results in a fixed charge over the useful life of the asset if its residual value does not change. The declining balance method results in a decreased expense over the useful life of the asset. The number of units method produces loading based on the use or output